2003
DOI: 10.1177/021849230301100108
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Affect Outcome of Cardiac Surgery in Octogenarians?

Abstract: The long-term results of cardiac surgery in 212 consecutive octogenarians (116 men, 96 women) were reviewed retrospectively. Preoperative functional status, Euroscore, and the incidences of hypertension and chronic obstructive pulmonary disease were similar in both sexes. Women had more diabetes mellitus (45% versus 25%; p < 0.05) but less renal dysfunction (16% versus 29%; p < 0.05). Men required emergency procedures more frequently (p < 0.05). Women underwent complete revascularization more often and had mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Two of them were large European multi-country studies that involved more than one CEE country [45,46]. Overall 152 reports on country level results were obtained: Austria (n=11) [47][48][49][50][51][52][53][54][55][56][57], Bulgaria (n=6) [45,46,58,59,13], Czech Republic (n=18) [60,61,45,46,[62][63][64][65][66]20,[67][68][69][70][71][72][73][74], Hungary (n=47) [11,75,76,45,[77][78][79][80][81][82][83][84][85][86]…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of them were large European multi-country studies that involved more than one CEE country [45,46]. Overall 152 reports on country level results were obtained: Austria (n=11) [47][48][49][50][51][52][53][54][55][56][57], Bulgaria (n=6) [45,46,58,59,13], Czech Republic (n=18) [60,61,45,46,[62][63][64][65][66]20,[67][68][69][70][71][72][73][74], Hungary (n=47) [11,75,76,45,[77][78][79][80][81][82][83][84][85][86]…”
Section: Search Resultsmentioning
confidence: 99%
“…In one study, the EQ VAS scale was modified to range from 0 to 10 [173]. Alternative scoring techniques occurred in some studies; for example, the ordinal numeric labels for the health state levels in the instrument (1-3 or 1-5) were treated as cardinal values that can be summed [51,90,95,163,54,116,126,131,65,171,173], which is a flawed concept because these numbers have no intrinsic arithmetic properties. Another study expressed the EQ-5D index score as a percentage [72], which can be misleading when considering the possible negative values.…”
Section: Methodological Deficiencies In Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 25–33 One study found lower scores in the physical domains of the study population. 34 Two studies reported poorer outcomes in women, 35 36 however a third paper revealed the opposite. 29 Three studies compared postoperative QoL in octogenarians against a younger patient cohort.…”
Section: Resultsmentioning
confidence: 99%